Uji Efektivitas Ulat Hongkong (Tenebrio molitor L.) dalam Degradasi Sampah Plastik Oriented Polypropylene - Estin Nofiyanti; Rubiansyah Dio Lazuardi; Melly Mellyanawaty; Gatut Ari Wardani (Rekayasa, 2023)
Oriented Polypropylene (OPP) plastic is a thermoplastic polymer that is widely used for the benefit of plastic product packaging in the pharmaceutical, cigarette, shampoo, detergent, textile, food, and beverage industries. OPP plastic has a high coefficient of thermal expansion, is susceptible to UV degradation, has poor resistance to solvents, is difficult to paint due to poor bonding properties, is highly flammable, susceptible to oxidation, and difficult to decompose naturally when it becomes waste. This study aimed to determine the ability of the Hong Kong caterpillar to degrade OPP plastic waste. This research method used a completely randomized design consisting of 4 treatments and 3 replications. The various treatments given were OPP 0.23 g for 120 caterpillars (V0); OPP 0.17 g: Bran 0.23 g for 120 caterpillars (V1); OPP 0.11 g: Bran 0.23 g for 120 caterpillars (V2); and OPP 0.06 g: Bran 0.23 g for 120 caterpillars (V3). The results showed that the feeding of OPP and rice bran affected the degradation rate of OPP plastic. The highest percent degradation value was obtained in the V3 treatment at 50% and the most optimal biodegradation rate occurred in the V1 treatment of 0.02 mg/day.